Landau Damping in Finite Regularity for Unconfined Systems with Screened Interactions. Issue 3 (16th November 2017) - Bedrossian, Jacob; Masmoudi, Nader; Mouhot, Clément
Abstract : We prove Landau damping for the collisionless Vlasov equation with a class of L 1 interaction potentials (including the physical case of screened Coulomb interactions) on ℝ x 3 × ℝ v 3 for localized disturbances of an infinite, homogeneous background. Unlike the confined case T x 3 × ℝ v 3, results are obtained for initial data in Sobolev spaces (as well as Gevrey and analytic classes). For spatial frequencies bounded away from 0, the Landau damping of the density is similar to the confined case. The finite regularity is possible due to an additional dispersive mechanism available on ℝ x 3 that reduces the strength of the plasma echo resonance.© 2017 Wiley Periodicals, Inc.